Effect of tillage, crop residue and phosphorus management practices on the productivity and profitability of maize (Zea mays) cultivation in Inceptisols - KUMAR, AMIT; BEHERA, U K; DHAR, SHIVA; SHUKLA, LIVLEEN; BHATIYA, ARTI; MEENA, M C; GUPTA, GAURENDRA; SINGH, RAMESH KUMAR (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted during kharif seasons of 2016–17 and 2017–18 at the research farm of ICAR–Indian Agricultural Research Institute, New Delhi to evaluate the effect of tillage, residue and phosphorus management practices on the growth, yield attributes, yield and economics of maize (Zea mays L.). The experiment comprised 15 treatment combinations laid out in a split–plot design with three replications. The main–plot treatments included three different tillage practices : CT–R (Conventional tillage with no residue), ZT–R (Zero tillage with no residue), ZT+R (Zero tillage with residue @ 2.5 t/ha for both maize and wheat) and sub–plot treatments included five phosphorus management practices: P1 (Control–NK as per recommendation, but no P), P2 (17.20 kg P/ha), P3 (17.20 kg P/ha + PSB), P4 (17.20 kg P/ha + Compost inoculants) and P5 (34.40 kg P/ha). Results revealed that, among the tillage practices, ZT+R found significant effect on growth and yield attributes of maize compared to CT–R during both the years of experiment. Different phosphorus management practices, application of 34.40 kg P/ha significantly improved the growth and yield attributes of maize compared to control treatment during both the years. Combined use of conservation agricultural practices (zero tillage with crop residue retention of 2.5 t/ha both the crops) along with application of 34.40 kg P/ha resulted significantly higher grain yield (6.40 and 6.49 t/ha), gross returns (105 and 114 ×103 `rs./ha) and net returns (64 and 72 ×103 rs.`/ha) during both the years of experiment but B:C ratio was maximum under combination of ZT–R with application of 34.40 kg P/ha during both the years.